2013
DOI: 10.1539/joh.12-0286-oa
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Psychosocial Work Conditions in Taiwanese Employees by Gender and Age from 2001 to 2010

Abstract: Changes in Psychosocial Work Conditions in Taiwanese Employees by Gender and Age from 2001 to 2010: Yawen CHENG, et al. Institute of Health Policy and Management, College of Public Health, National Taiwan University, Taiwan— Objective The aim of this study was to examine changes in working hours, shift work, psychological and physical job demands, job control and job insecurity in Taiwanese employees by gender and age during the period of 2001 to 2010. Methods The study subjects were 36,750 men and 27,549 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
(21 reference statements)
4
21
1
Order By: Relevance
“…The differential changes according to age, occupation, public/private sector, work contract and selfemployed/employee status have almost never been studied before. In the Taiwanese study by Cheng and al., analyses were stratified on age but no test was performed to assess whether the changes were different according to age (Cheng et al 2013). In line with our study, they found that job control and psychological demands seemed to deteriorate more for younger and middle age workers.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The differential changes according to age, occupation, public/private sector, work contract and selfemployed/employee status have almost never been studied before. In the Taiwanese study by Cheng and al., analyses were stratified on age but no test was performed to assess whether the changes were different according to age (Cheng et al 2013). In line with our study, they found that job control and psychological demands seemed to deteriorate more for younger and middle age workers.…”
Section: Discussionsupporting
confidence: 82%
“…The analyses were powerful enough to allow stratification by gender something that may be considered fundamental (Niedhammer et al 2000), and to observe differential changes according to several covariates. To date, only three previous studies explored the differential changes in psychosocial work factors according to age (Cheng et al 2013), occupation (Malard et al 2013), and gender, age, occupational skill level and employment arrangements (a combination of work contract, selfemployed status and working time) but only for job control and job security (LaMontagne et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social support (i.e., workrelated support from supervisors and colleagues) might not only be a source of pressure, but could also have a regulating effect on individuals' psychological job stressors (Y. Cheng, Chen, Burr, Chen, & Chiang, 2014).…”
Section: Literature Review Job Characteristics and Web-based Learningmentioning
confidence: 99%